PURIFICATION OF SPERMATOGONIAL STEM CELLS FROM RAM TESTICULAR ISOLATE USING FICOLL DENSITY GRADIENT SEPARATION - BINSILA, B K; SELVARAJU, S; GHOSH, S K; PRASAD, J K; RAMYA, L; RAVINDRA, J P; BHATTA, R (The Indian Journal of Animal Reproduction, 2022)
Spermatogonial stem cells (SSCs) can be used to propagate male superior germ plasm and to preserve the male of high genetic merit and endangered species. The objective was to assess the efficiency of different Ficoll density gradient separation in order to purify SSCs from the testicular cell isolates. The mixed testicular isolates obtained after enzymatic digestion of testicular tissues was subjected to two different Ficoll density gradient methods (method 1: Ficoll at 10 and 12% and method 2: Ficoll at 10, 12 and 16%). The percentage of SSCs (positive for PLZF, an SSC marker) obtained from the fractions, F12 media and F12-16 Interphase (FI) yielded (p<0.05) higher percentage of PLZF+ spermatogonia as compared to initial testicular isolate (35.1±3.8 and 22.8±4.5 vs 11.2±3.7). The viability (%) of F12 and FI enriched fraction was 55.6±4.3 and 51.2±6.5, respectively. In brief, Ficoll purification method using F12 fraction yielded higher (p<0.05) recovery rate (4.9±1.2x106 cells/g of testis) with improved purity (1.8±0.4x106 PLZF+ cells) when compared to FI (recovery rate: 3.28±1.2x106 cells/g of testis and purity: 0.8±0.3x106 PLZF+ cells) and can be used either alone or in combination with other purification methods for further enrichment of SSCs that can be used for culture.